Upaya Pengembangan Agroforestry Sebagai Langkah Pengamanan Peyangga Hutan Di Kabupaten Pidie Jaya - Ahmad Humam Hamid; Romano Romano (Jurnal Agrisep, 2013)
ABSTRACT. This research was aimed to : analyze Agrpforestry policy and effect of community social economic factors in conducting agroforestry consenssionin Pidie Jaya District. The research uses survey method with Multi Stage Cluster Sampling. The research was carried out in Pidie Jaya District right in Bandar Baru,Trienggadeng, and Pante Raja Sub-districts. The research result revealed that police of agroforestry does include the local community. The obstacle in agroforestry policy such as unjustice of policy more emphasized of economic factor, assumption of forest is public matter, consention authority still be handled by central government, and anthropocentrism attitude on forest. Policy directive of agroforestty consenssion in Pidie Jaya District can be done by establishing area of cacao and havea plantation in buffer zone, and also giving conservation concession to broken forest, critical, and degradated. Factors that correlated very tight to forest degradation are law enforcement cultivation land wide, residence status, and security condition.